Analytical study of nonlinear water wave equations for their fractional solution structures - Zafar, Asim; İnç, Mustafa; Shakeel, Muhammad; Mohsin, Muhammad (World Scientific Publ Co Pte Ltd, 2022)
This paper examines the three-dimensional nonlinear time-fractional water wave equations for their analytical wave solutions. These are the equations of the names (3 + 1)-Zakharov-Kuznetsov-Burgers equation and (3+1)-Yu-Toda-Sasa-Fukuyama equation. The obtained wave solutions are in the form of kink, periodic and singular waves by utilizing the (G'/G(2))-expansion approach. The aforesaid solutions are verified and demonstrated graphically via symbolic soft computations.
Keywords: Zakharov-Kuznetsov-Burgers equation; Yu-Toda-Sasa-Fukuyama equation; wave solutions